Tujuan Ekonomi Islam Terhadap Implementasi Akad Salam dalam Transaksi Jual Beli Online di Marketplace Tiktok - Ridhoan Damara; Idwal; Katra pramadeka (Masyarakat Ekonomi Syariah Bogor, 2025)
This study discusses the implementation of the salam contract in online buying and selling transactions on the TikTok marketplace and its relevance to Islamic economic principles. Using a qualitative descriptive method with interviews and observations, the research reveals that salam contracts are commonly applied in pre-order transactions, where full payment is made before the goods are delivered. The study identifies several challenges, including delivery delays, product discrepancies, and limited Sharia-compliant payment options. Nevertheless, the application of salam offers transaction security and predictability. The study recommends more transparent product specifications, stricter regulations, and effective dispute resolution mechanisms to align with the goals of Islamic economics.